Titanium imido complexes containing 1,3,5-triazacyclohexane ligands - Wilson, P; Blake, A; Mountford, P; Schroder, M (2000)
The syntheses of the 1,3,5-trimethyl- and tri-tert-butyl-1,3,5-triazacyclohexane-supported imido complexes [M(NR)(R′ 3tach)Cl 2] (M = Ti or Zr (NMR only); R = Bu t or 2,6-C 6H 3Pr i2; R′ = Me or Bu t) are reported, along with that of the thermally robust dibenzyl derivative [Ti(NBu t)(Me 3tach)(CH 2Ph) 2]. The tert-butylimido ligand in [Ti(NBu t)(Me 3tach)Cl 2] undergoes exchange with ArNH 2 (Ar = 4-C 6H 4Me or 2,6-C 6H 4Me or 2,6-C 6H 3Pr i2) to form the corresponding arylimides [Ti(NAr)(Me 3tach)Cl 2]. The Me 3tach ring in [Ti(NR)(Me 3tach)Cl 2] undergoes slow exchange with Bu t3tach or Me 3tacn (1,4,7-trimethyl-1,4,7-triazacyclononane) to give the ring-exchanged products [Ti(NR)(Bu t3tach)Cl 2] and [Ti(NR)(Me 3tacn)Cl 2], respectively. The complexes [Ti(NR)(Me 3tach)X 2] (R = Bu t or 2,6-C 6H 3Pr i2; X = Cl or CH 2Ph) exhibit room-temperature dynamic NMR behaviour via an unusual trigonal twist of the facially coordinated Me 3tach ligand, and the activation parameters for these processes have been measured and are discussed. The X-ray structures of [Ti(NR)(Bu t3tach)Cl 2] (R = Bu t or 2,6-C 6H 3Pr i2) and [Ti(NBu t)(Me 3tach)(X) 2] [X= Cl or CH 2Ph) are reported. Me 3tach and Bu t3tach = 1,3,5-trimethyl- and tri-tert-butyl-1,3,5-triazacyclohexane, respectively. © 2000 Elsevier Science S.A. All rights reserved.